Effect of Methionine on AMD1 Gene Expression in Prostate Cancer Cells. (18th August 2021) - Shen, Shaochen; Zeng, Linhong; Huang, Hongwei
Abstract: Objective: To investigate the effect of AMD1 gene expression on prostate cancer cells (PC-3M), explore the mechanism of AMD1 action in cancer cells, and examine the regulation of AMD1 gene expression by methionine (MET). Methods: Quantitative PCR (qPCR) and western blot analysis (WB) approaches were used to detect and measure gene expression. The cell apoptotic rate was determined by flow cytometric (FCM) analysis. Results: qPCR and WB assays showed that both AMD1 gene expression and cell apoptotic rate were associated with MET. Conclusion: MET has a significant regulatory effect on the expression of the AMD1 gene and a certain amount of MET can promote the expression of the AMD1 gene. This provides a health guideline for a low-methionine diet for prostate cancer patients and scientific evidence for prostate cancer prevention.